Pengembangan Model Media Pembelajaran untuk Meningkatkan Pemahaman Konsep Teknik Dasar Renang pada Siswa melalui Vitual Reality - Syahril Adam; Zainul Aziz; Andi Ade Surya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop virtual reality-based learning media to improve students' understanding of basic swimming techniques. The research and development method was applied, involving students at State Senior High School 10, East Halmahera. The feasibility test results showed that 80% of respondents gave the developed VR media a